1969
DOI: 10.1172/jci106198
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipases in arterial tissue

Abstract: A B S T R A C T The role of phospholipases in the regulation of the changing phospholipid composition of normal human aortae with age was studied. Portions of grossly and histologically lesion-free ascending aortae from 16 females and 29 males obtained at autopsy, were analyzed for deoxyribonucleic acid (DNA), phospholipid, and cholesterol content and phospholipid composition. Enzymic activity toward four substrates, lecithin (LE), phosphatidyl ethanolamine, lysolecithin, and sphingomyelin (SP), was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In vitro studies showed that the net uptake (Table V) of lysolecithin by atherosclerotic intima plus inner media was greater than that in control tissue, When no lysolecithin was added to the incubation medium, the quantity of ly- (2,11,16). The presence of albumin or other plasma proteins in the incubation medium containing lysolecithin greatly inhibited the rate of transfer of lysolecithin to the aorta (see also ref.…”
Section: Metabolism Of Lysolecithin By the Arterial Wallmentioning
confidence: 95%
“…In vitro studies showed that the net uptake (Table V) of lysolecithin by atherosclerotic intima plus inner media was greater than that in control tissue, When no lysolecithin was added to the incubation medium, the quantity of ly- (2,11,16). The presence of albumin or other plasma proteins in the incubation medium containing lysolecithin greatly inhibited the rate of transfer of lysolecithin to the aorta (see also ref.…”
Section: Metabolism Of Lysolecithin By the Arterial Wallmentioning
confidence: 95%
“…LDL extracted from human atherosclerotic lesions has higher SM levels than LDL from plasma (Hoff and Morton, 1985; Guyton and Klemp, 1996; Schissel et al, 1996, 1998). A substantial amount of the SM found in arteries and atherosclerotic lesions appears to arise from SM synthesis in the arterial tissues (Zilversmit et al, 1961; Eisenberg et al, 1969). Plasma SM levels in atherogenic apoE KO mice are fourfold higher than in wild type mice (Jeong et al, 1998) and this may contribute to the increased atherosclerosis (Plump et al, 1992; Zhang et al, 1992).…”
Section: Involvement Of Sphingolipid Metabolism In Development Of Chrmentioning
confidence: 99%
“…Since all the enzymes of the lipolytic pathway and the adenyl cyclase system are found in the arterial wall (17)(18)(19)(20)(21)(22)(23)(24)(25), it is possible that the site of action of TMO is in the arterial wall. However, the interrelation of the adenyl cyclase system and lipolysis has been more completely delineated in liver and adipose tissue and an action at these sites might also, indirectly, prevent lipid accumulation in arterial plaques.…”
Section: Fig 1 Mean Plasma Total Cholesterolmentioning
confidence: 99%